Inkblot personality test : understanding the unconscious mind - Dubey, B. L. (Bankey Lal), 1943-; Banerjee, Padmakali; Dubey, Anand (Sage Publications, 2019)
Provides a comprehensive understanding of projective psychological techniques to understand the unconscious mind.